The Hanseatic League and Education - A Neglected Chapter in European and German History - Olga Graumann; Sören Affeldt (International Dialogues on Education: Past and Present, 2020)
The focus of this article is on the connection between education and the Hanseatic League, a topic largely neglected in educational literature, although the qualification needs of Hanseatic merchants had a remarkable influence on the development of German and European education. The Hanseatic League as a network between merchant families, friends and trading partners, its temporal limitation from about the12th to the 17th century, its spatial expansion, its offices at home and abroad as well as its trading goods are discussed in detail. The main part of the article is dedicated to education. The general history of education in the Middle Ages cannot be separated from the specific history of merchant education. However, it can be stated that both strands of development have mutually fertilized each other. Of particular interest for today's educational processes is the importance of "learning abroad" to learn foreign languages and get to know foreign cultures, as well as the "learning by doing" that characterized the education of merchants in the Middle Ages. Since the Hanseatic League has been misused in the field of education for political ideologization over the past two centuries, a brief overview of the reception of the Hanseatic League in the history of education is appropriate. The topic is rounded off by emphasizing the importance of the European Hanseatic Museum in Lübeck, founded in 2015, for education today.